Penyuluhan Digital Untuk SMP YWKA 2 - Nia Liska Saputri; Sigit Widiyarto; Nugroho Nugroho; Irfan Hadi (Jurnal Pengabdian UntukMu NegeRI, 2022)
This Community Service activity aims to introduce Schoology as a digital classroom platform to improve the quality of educators in teaching. This activity involved two lecturers and one student from Indraprasta University PGRI. The target participants of this community service activity are junior high school educators Yayasan Wanita Kereta Api II Jakarta. This activity was attended by 11 teachers of SMP YWKA 2 Pulogadung, East Jakarta. The approach used is Andragogy. Andragogy as the art and science of helping students (adults) to learn, the science and arts of helping adults learn (Knowles, 1970). The practice and discussion methods used can help facilitate participants' understanding. This activity went smoothly without any significant obstacles.. Keywords: Schoology, digital classroom, Andragogy